Hydrophobic removal agent of nonionic surfactant as well as preparation method and application of hydrophobic removal agent
The hydrophobic remover coated with boric acid and sol coated hydrophobic remover solved the problem of nonionic surfactant removal in sulfolane, achieved efficient depth removal and reduced sulfolane loss rate, and ensured the natural gas purification process Stability and economy.
Patent Information
- Application Number
- CN202310735675.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-06-20
AI Technical Summary
The prior art is difficult to effectively remove non-ionic surfactants in sulfolane, which leads to foaming of the desulfurization solution, affecting the stability and product quality of the natural gas purification process. The existing removal technology has a high loss rate on sulfolane and may introduce new impurities. Reduce desulfurization performance.
Porous polymer microspheres are used as hydrophobic detachants to prepare by copolymerization of acrylate monomers, aliphatic diene crosslinking agents and pore-generating agents, loading boric acid, and preparing sols with silicates and alkoxy silicones Coating to form a highly selective detachant, deeply remove non-ionic surfactant, reduce sulfolane loss, and avoid the introduction of new impurities.
The efficient and deep removal of non-ionic surfactants in sulfolane is achieved, which reduces the sulfolane loss rate of the desulfurizer, maintains the stability and performance of the desulfurization solution, and does not introduce new impurities, which significantly improves the economics of the desulfurization process and Environmental protection.
Smart Images

Figure BDA0004300089070000052 
Figure BDA0004300089070000201 
Figure BDA0004300089070000221
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer functional materials, and in particular to a hydrophobicity removing agent for a nonionic surfactant, and a preparation method and application thereof. Background Art
[0002] Many raw natural gases extracted from underground reservoirs contain impurities such as H2S and organic sulfur and cannot be used directly. They must be desulfurized and purified before they can become commercial natural gas. Commercial natural gas specifies the sulfur content, and the total sulfur index is currently required to be ≤20mg / m 3 .
[0003] Organic sulfur removal technology must be used to control the organic sulfur content in the product natural gas to a very low level to achieve a total sulfur content of ≤20mg / m 3 Therefore, the demand for organic sulfur removal technology and organic sulfur removal solution in the field of natural gas purification is rapidly increasing.
[0004] Sulfolane is an excellent solvent for organic sulfur, with a high organic sulfur removal rate. Sulfolane is used as the preferred solvent for removing organic sulfur from natural gas. The number of purification plants using sulfolane and physical and chemical desulfurization solutions based on sulfolane is increasing rapidly.
[0005] During the natural gas purification process, the desulfurization solution is easily contaminated and deteriorated by the residues of upstream mining operations. The contaminated and foamed desulfurization solution is the most common and widespread problem in the natural gas purification production process, and is the main factor restricting the stable production and increase of the natural gas purification process. Therefore, the amine liquid resurrection technology that can remove the foaming pollutants in the desulfurization solution and restore the performance of the desulfurization solution is a key technology to ensure the stable production of the natural gas purification plant. However, when the existing amine liquid resurrection technology is used for cyclopentane sulfone and cyclopentane-based physical and chemical desulfurization solutions, it cannot effectively separate the foaming substances therein. The contaminated and foamed desulfurization solution leads to unqualified product natural gas quality, unstable operation of the natural gas purification device, and shutdown. These problems cannot be solved, which seriously affects normal production. Therefore, the demand for the removal technology of foaming substances in cyclopentane sulfone in the field of natural gas purification is very urgent.
[0006] Various surfactants in the residues of natural gas extraction operations are the cause of the foaming of the desulfurization solution. For example, non-ionic surfactants are used in foaming, demulsification, corrosion inhibition, drilling, and oil displacement agents. To solve the problem of foaming in the desulfurization solution, these surfactants must be removed.
[0007] Anionic and cationic surfactants can be ionized in aqueous solution, and their ionization is very different from that of sulfolane. After adding water to sulfolane, the interaction between anionic and cationic surfactant molecules and sulfolane molecules becomes weak, so the development of anionic and cationic surfactant removers in sulfolane can find a technical breakthrough from these property differences; however, the polarity, magnetism, ionization, organicity and inorganicity of non-ionic surfactants are extremely similar to those of sulfolane molecules, and the affinity between them and sulfolane molecules is very strong. It is very suitable to select sulfolane for extracting non-ionic surfactants, but it is very difficult to separate non-ionic surfactants from sulfolane. Various existing adsorbent materials have no selectivity for the adsorption of sulfolane and non-ionic surfactants. In the presence of high-concentration sulfolane (the concentration of sulfolane in the physical and chemical desulfurization solution is 50 times or more than the concentration of non-ionic surfactants), the removal rate of non-ionic surfactants is extremely low, less than 10%, and the removal rate by distillation is also very low, less than 30%. Because a few hundred ppm of surfactant can cause severe foaming in the desulfurization solution, the depth of surfactant removal in the desulfurization solution is very high. The separation of sulfolane and surfactant is difficult to achieve, and deep removal is even more difficult. Therefore, sulfolane has been used in the field of natural gas purification for many years, and the problem of how to revive it after being contaminated and foamed has not been solved. The only way to restore production is to replace the new solvent, and the contaminated solution replaced out of the device is treated as waste liquid. The waste liquid generated by a single desulfurization device due to contamination is usually as high as more than 400 tons. Because the organic content of sulfolane desulfurization solution is as high as 70% or more, and it also contains toxic components such as hydrogen sulfide, it is a hazardous waste that is very difficult and expensive to dispose of, which has caused a great economic burden and environmental pressure on the purification plant.
[0008] Existing purification technologies for deteriorated sulfolane include ion exchange separation, precipitation separation, activated carbon adsorption, and decomposition. 1) Ion exchange separation, using anion exchange resin to purify deteriorated sulfolane, such as patents US5053137, CN1230545A, CN1644581A, CN1076726C, CN1125063C, CN111111306A, CN1861594A, etc. The anion exchange resin used is a styrene-divinylbenzene polymer containing primary, secondary amine or quaternary ammonium groups. The anion exchange resin can only remove substances in ionic state in the solution. Nonionic surfactants are not ionized in water and sulfolane, so they cannot be removed by ion exchange resins. 2) Precipitation separation method, such as patent US4820849, adding polyacid or polyacid anhydride to sulfolane solvent to form solid precipitation with acidic impurities; alkali adsorption separation method, such as Japanese patents 7-278316, CN1634917A, CN106957297A, using alkali metal or alkaline earth metal oxides, hydroxides, carbonates to adsorb acidic impurities in sulfolane. These two methods can only remove acidic impurities in sulfolane, and non-ionic surfactants are not acidic substances, so these two methods cannot remove non-ionic surfactants. 3) Activated carbon adsorption method, Japanese patent 7-101953 uses activated carbon and tiny fibrous natural cellulose to remove suspended particles and dissolved ionic impurities. Activated carbon has no selectivity for the adsorption of sulfolane and nonionic surfactants, and the selectivity ratio is less than 2. The concentration of sulfolane in the sulfolane desulfurization solution is much higher than that of nonionic surfactants. Due to the concentration advantage, it will occupy the activated carbon adsorption surface before the nonionic surfactants, making it saturated quickly, resulting in a nonionic surfactant removal rate of less than 10%. 4) Decomposition method, CN213885678U decomposes part of the acidic substances of sulfolane by adding monoethanolamine. Nonionic surfactants cannot be decomposed by monoethanolamine, so it is not applicable.
[0009] The existing purification technologies for deteriorated desulfurization solutions include: ion exchange, electrodialysis, vacuum distillation, activated carbon adsorption separation and foaming impurity removal technology. Among these technologies, ion exchange and electrodialysis can only remove salt impurities in desulfurization solutions, such as US6517700, US5162084, US5788864, CN1733355A, CN1230545A, CN102189008A; vacuum distillation has a high sulfolane loss rate and a low removal rate of non-ionic surfactants; activated carbon adsorption separation and the foaming impurity removal technology independently developed by Southwest Oil and Gas Field Branch have no selectivity for the adsorption of sulfolane and non-ionic surfactants, and the removal rate of non-ionic surfactants is less than <10%.
[0010] At present, the treatment methods of non-ionic surfactant wastewater mainly include foam separation method, adsorption method, biological method, micro-electrolysis method, Fenton oxidation method, etc. Foam separation method is a more commonly used physical method, which separates the foam by bubbling to remove the non-ionic surfactant in the foam. This method has the advantages of easy operation and can also achieve the purpose of separating non-ionic surfactants. However, for the sulfolane desulfurization solution with severe foaming, the whole solution foams after bubbling, and after the foam separation is removed, sulfolane also loses 80 to 90 percent. For example, patent CN107935236A uses adsorbent material particles to adsorb the surfactant in the wastewater, and then bubbling allows the adsorbent material particles of the adsorbent to be enriched on the wastewater liquid surface and then removed. Adsorbent material particles include silicon dioxide, calcium carbonate, calcium sulfate, activated carbon particles, magnetite powder, hematite powder, titanium dioxide, clay ore, fly ash or phosphate tailings powder, and iron tetroxide, silicon dioxide, titanium oxide, zinc oxide metal oxide nanoparticles synthesized by wet chemistry, silicon dioxide and titanium dioxide with amino or carboxyl modified surfaces, polystyrene resin particles, phenolic resin particles or melamine resin particles, unmodified polystyrene resin particles, unmodified phenolic resin particles or unmodified melamine resin particles. These adsorbent materials have no selective absorption for sulfolane and non-ionic surfactants, and not only have a low removal rate for non-ionic surfactants in sulfolane, but also a large loss of sulfolane. Adsorption method, "Research on the Treatment of Non-ionic Surfactant Wastewater with Modified Fly Ash" introduces that fly ash is modified with hydrochloric acid, sulfuric acid and other reagents to obtain fly ash adsorption coagulant, and then the modified fly ash adsorption coagulant is used to treat wastewater containing non-ionic surfactant alkylphenol polyoxyethylene ether. The results show that the modified fly ash has good adsorption performance for wastewater containing alkylphenol polyoxyethylene ether with a concentration of 300-1800 mg / L; however, the modification process requires the addition of hydrochloric acid, sulfuric acid and other reagents, which will cause hydrochloric acid and sulfuric acid to flow into the wastewater during wastewater treatment, causing secondary pollution and increasing the difficulty of subsequent wastewater treatment. This method that causes secondary pollution is even worse for sulfolane. The introduction of hydrochloric acid and sulfuric acid into sulfolane will not only cause corrosion problems, but also cause its desulfurization performance to deteriorate or even completely fail, so it is not applicable. The biological method is a method of using microorganisms to use non-ionic surfactants as carbon sources to degrade non-ionic surfactants in wastewater. Sulfolane and other organic substances are also organic matter and will be degraded at the same time, so it is not applicable. The micro-electrolysis method is based on the principle of electrochemistry. It forms an electrode reaction in the wastewater to cause non-ionic surfactants to undergo catalytic oxidation decomposition, coagulation, adsorption, complexation and replacement reactions, thereby quickly removing pollutants. The Fenton oxidation method uses the ferrous ions in the Fenton reagent as a catalytic initiator. Under its action, H2O2 produces a large number of free radicals, which further accelerates the initiation reaction of the free radical chain, thereby quickly degrading and removing the non-ionic surfactants in the wastewater.These two methods are usually used in combination, such as patents CN110357357A, CN1508077A, CN104310665, and CN109626675A. These methods require the addition of acid to adjust the pH to 0.5-5, and then introduce iron ions and ferrous ions, which are not suitable for sulfolane because the addition of acid will reduce its desulfurization performance or even completely fail, increase its corrosiveness, and the precipitation of iron ions and ferrous ions after contact with hydrogen sulfide will cause the desulfurization device to be blocked.
[0011] In summary, the removal rate of nonionic surfactants in sulfolane by the existing technologies is very low, less than 30%, there is no selectivity for the removal of sulfolane and nonionic surfactants (selection ratio <2), the loss rate of sulfolane is high, and some technologies may introduce new impurities into the solution, causing the desulfurization performance to deteriorate and the corrosiveness to increase. Summary of the invention
[0012] One object of the present invention is to provide a hydrophobic remover for nonionic surfactants and a preparation method thereof. The hydrophobic remover of the present invention has high selectivity for nonionic surfactants and sulfolane, and can remove nonionic surfactants from sulfoneamine-containing solutions.
[0013] Another object of the present invention is to provide an application of the hydrophobic remover of the non-ionic surfactant, especially in the deep removal of the non-ionic surfactant in the sulfone amine solution.
[0014] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0015] In one aspect, the present invention provides a method for preparing a hydrophobicity removing agent for a nonionic surfactant, wherein the preparation method comprises the following steps:
[0016] Suspending and copolymerizing an acrylate monomer, an aliphatic diene crosslinking agent and a porogen in water to obtain porous polymer microspheres; soaking the porous polymer microspheres in a boric acid solution to load boric acid, and then filtering out the microspheres and drying them;
[0017] The surface of the porous polymer microspheres loaded with boric acid is coated with sol, and then aged to obtain the hydrophobic removal agent;
[0018] The sol is prepared from silicate and alkoxy silicon by a sol-gel method, wherein the structural formula of the alkoxy silicon is Wherein, R1 is a C1-C10 alkyl group, and R2 is a C5-C20 fluoroalkyl group.
[0019] Specifically, the active component boric acid in the pores of the porous polymer microspheres can be complexed with the nonionic surfactant entering, but not with sulfolane, thereby achieving selective adsorption of the two, achieving deep removal of the nonionic surfactant in sulfolane, and low sulfolane loss rate; at the same time, it can ensure that no new impurities are introduced after the nonionic surfactant in sulfolane is removed. Further, the sol is modified and coated to be hydrophobic, which has a repelling effect on water molecules. When it is applied to the removal of nonionic surfactants in sulfoneamine desulfurization solution, the contact probability between boric acid in the remover and water molecules in the desulfurization solution is greatly reduced. The high organic molecule permeability of the colloid can ensure that the nonionic surfactant molecules pass through the colloid and come into contact with the boric acid to be removed.
[0020] In some embodiments of the present invention, preferably, the silicate is ethyl orthosilicate.
[0021] In some embodiments of the present invention, preferably, in the alkoxy silicon, R1 is a C1-C5 alkyl group, and R2 is a C9-C17 fluoroalkyl group.
[0022] In some embodiments of the present invention, more preferably, R1 is methyl, ethyl or propyl.
[0023] In some embodiments of the present invention, more preferably, R2 is nonafluorohexyl, tridecafluorooctyl or heptadecafluorodecyl.
[0024] In some embodiments of the present invention, most preferably, R2 is heptadecafluorodecyl.
[0025] In some embodiments of the present invention, preferably, the structural formula of the acrylate monomer is:
[0026]
[0027] Wherein R is a C1-C5 alkyl group; preferably, the acrylate monomer is methyl acrylate or hexyl acrylate, more preferably hexyl acrylate.
[0028] Sulfolane has a weak affinity for chain alkane molecules and a strong affinity for aromatic molecules. Therefore, the present invention does not select commonly used styrene as a monomer, but uses acrylate as a monomer. At the same time, the ester group in acrylate has a certain adsorption effect on sulfolane, but the alkyl group has a shielding effect on the effect of the ester group adsorbing sulfolane. The more carbon atoms in the alkyl group, the greater the shielding effect. However, if the number of alkyl groups is too large, a longer polyacrylate segment and a linear acrylate homopolymer may be generated during the polymerization reaction, causing the prepared remover to agglomerate during use. Among them, the number of alkyl groups in the hexyl acrylate molecule can best take into account the solution of the above two problems, satisfying that the shielding effect is large enough to have a very weak adsorption effect on sulfolane, and the remover will not agglomerate during use. Therefore, the acrylate monomer of the present invention is preferably hexyl acrylate.
[0029] In some embodiments of the present invention, preferably, the aliphatic diene crosslinking agent is ethylene glycol dimethacrylate.
[0030] The polymer stripping agent of the present invention selects aliphatic diene as a crosslinking agent, and does not select conventional phenyl-containing divinylbenzene as a crosslinking agent because phenyl can adsorb cyclopentane. The preferred ethylene glycol dimethacrylate can increase the swelling degree of the copolymer, and the interchain distance of the finally obtained polymer is conducive to the penetration of nonionic surfactants with larger molecular weight.
[0031] In some embodiments of the present invention, preferably, the porogen is selected from at least one of isooctyl alcohol, n-decane, decanol, and 2-ethyl-1-hexanoic acid.
[0032] The pore size of the micropores prepared by using isooctyl alcohol, n-decane, decanol, and 2-ethyl-1-hexanoic acid is suitable for the subsequent introduction of the active component boric acid, but the pore size is not too large to weaken the potential energy superposition effect of each plane. Other porogens will either result in a low loading amount of the active component boric acid, or lead to weak adsorption of non-ionic surfactants, resulting in a small amount of adsorbed non-ionic surfactants being resolved.
[0033] In some embodiments of the present invention, preferably, the molar ratio of the acrylate monomer, the aliphatic diene crosslinking agent, and the porogen is 1:(0.07-0.3):(0.1-0.8).
[0034] When the amount of cross-linking agent is higher than 0.3, the internal structure of the porous polymer microspheres will be too tight, which will increase the shuttling resistance of non-ionic surfactant molecules inside the porous polymer microspheres, which is not conducive to adsorption or desorption during regeneration, and the removal rate is low. When the amount of cross-linking agent is lower than 0.07, the porous polymer microspheres will aggregate in the cyclopentane sulfone desulfurization solution. When the amount of porogen is lower than 0.1, the pore capacity and specific surface area of the porous polymer microspheres are too low, and the adsorption capacity of <10 mg / g does not meet the use requirements. When the amount of porogen is higher than 0.8, the porous polymer microspheres will have problems of poor strength and collapse of the internal pore structure.
[0035] In some embodiments of the present invention, more preferably, the molar ratio of the acrylate monomer, the aliphatic diene crosslinking agent, and the porogen is 1:(0.1-0.2):(0.5-0.6).
[0036] In some embodiments of the present invention, preferably, the porous polymer microspheres loaded with boric acid have a particle size distribution of 0.2 mm to 1.0 mm and a specific surface area of 300 m 2 / g~400m 2 / g, the average pore diameter of the porous polymer microspheres is 50nm-110nm, and the pore volume is 1.5mL / g-2.0mL / g.
[0037] In some embodiments of the present invention, preferably, the sol is prepared by the following steps:
[0038] The silicate is mixed with ethanol, then added into acidic water and mixed, and then alkoxy silicon is added and mixed for 8 hours to 12 hours, and then allowed to stand for 20 hours to 40 hours to obtain the sol.
[0039] Silicate esters and alkoxy silicon are hydrolyzed in water and then polymerized to form sol. Ethanol is added to make silicate esters and alkoxy silicon miscible with water. Acid is added to adjust the water to be acidic in order to control the gelation rate and obtain a sol with uniform particle size distribution. The molecular structure and size of alkoxy silicon are the key to determining the pore size of the formed colloid. The pore size of the colloid made of the defined alkoxy silicon is suitable for non-ionic surfactant molecules.
[0040] In some embodiments of the present invention, preferably, the molar ratio of the silicate to ethanol is 1:(3-8).
[0041] If the amount of ethanol is too large, not only the gelation speed is too slow, but also the particle size is too small. The hydrophobic remover made by using this sol has a low colloid permeability, which hinders the contact between the non-ionic surfactant molecules and the boric acid; if the amount of ethanol is too small, the silicate, alkoxy silicon and water cannot be miscible. Therefore, the preferred molar ratio of silicate to ethanol in the present invention is 1: (3-8).
[0042] In some embodiments of the present invention, preferably, the acidic water is adjusted to a pH of 1 to 6, more preferably 2 to 3, by adding acid dropwise into the water.
[0043] If the hydrolysis is too fast under alkaline conditions, the sol will easily condense into blocks. If the acid is too strong and the gel formation is too slow, the size of the formed colloid particles will be uneven, and the required particle size of 2nm to 3nm particles only accounts for 48%. When the pH value is 2 to 3, a sol with uniform particle size can be formed, and the particle size of 2nm to 3nm particles accounts for more than 80%.
[0044] In some embodiments of the present invention, preferably, the molar ratio of the silicate to water is 1:(0.5-1.1).
[0045] When the amount of water is too large (when the molar ratio of water to silicate is greater than 1.2), not only the gelation is slow, but also the viscosity of the formed sol is too low. The coating layer of the hydrophobic remover made by using this sol has the problem of falling off during use. When the amount of water is too low, the colloidal particles formed are uneven. Therefore, the preferred molar ratio of silicate to water in the present invention is 1: (0.5-1.1).
[0046] In some embodiments of the present invention, preferably, the molar ratio of the silicate to the alkoxy silicon is 1:(0.6-1.5).
[0047] When the molar ratio of alkoxysilane to silicate is lower than 0.6, the hydrophobicity of the prepared colloid is insufficient; when it is higher than 1.5, the pores formed are too large and the hydrophobicity of the colloid does not meet the requirements.
[0048] The preparation process of the porous polymer microspheres comprises: suspending and copolymerizing acrylate monomers, aliphatic diene crosslinking agents and porogens in water to obtain porous polymer microspheres; soaking the porous polymer microspheres in a boric acid solution to load boric acid, and then filtering out the microspheres and drying them.
[0049] In some embodiments of the present invention, preferably, the boric acid solution is a saturated boric acid solution at 80-90°C.
[0050] High concentration boric acid solution is conducive to the loading of boric acid, but the solubility of boric acid in cold water is very low. Increasing the temperature can increase its solubility; but when the temperature reaches above 90°C, the solution has a tendency to boil, which is not conducive to the deposition of boric acid on the microspheres. Therefore, the preferred boric acid solution of the present invention is a saturated boric acid solution at 80-90°C.
[0051] In some embodiments of the present invention, preferably, the mass ratio of the boric acid to the porous polymer microspheres is greater than 0.1. Too small an amount of boric acid will result in the adsorption capacity of the obtained stripping agent for nonionic surfactants being less than 10 mg / g, which does not meet the use requirements.
[0052] In some embodiments of the present invention, more preferably, the mass ratio of the boric acid to the porous polymer microspheres is 0.7:1.
[0053] In some embodiments of the present invention, preferably, the soaking time is >0.5 h.
[0054] In some embodiments of the present invention, more preferably, the soaking time is 5 h to 6 h.
[0055] When the immersion time is less than 0.5 h, the adsorption capacity of the obtained remover for nonionic surfactant is less than 10 mg / g and does not meet the use requirements. When the immersion time exceeds 6 h, the adsorption capacity of the remover no longer continues to increase.
[0056] In some embodiments of the present invention, preferably, the immersion temperature is 50-90° C., at which the solubility of boric acid is high. Above 90° C., the solution tends to boil, which is not conducive to the deposition of boric acid on the microspheres.
[0057] In some embodiments of the present invention, preferably, the drying temperature is 100-165°C.
[0058] In some embodiments of the present invention, more preferably, the drying temperature is 120-140°C.
[0059] When the drying temperature is higher than 165°C, boric acid tends to decompose into metaboric acid. 120-140°C can ensure drying without decomposing boric acid and shorten the drying time.
[0060] In some embodiments of the present invention, preferably, the specific process of the sol coating includes:
[0061] The porous polymer microspheres are arranged in a single layer in a container containing sol. The height of the sol in the container is 1 / 4 to 1 / 3 of the height of the remover particles. The porous polymer microspheres are rolled in the sol until the entire surface is covered with the sol, and the porous polymer microspheres are taken out.
[0062] The amount of sol applied should not be too much, otherwise the colloid on the surface of the stripper will be thicker, which will seriously reduce the adsorption rate of the non-ionic surfactant, resulting in insufficient removal rate. The colloid covering the surface of the microsphere should be as thin as possible, which is conducive to improving the rate and removal rate of the stripper adsorbing the non-ionic surfactant. At the same time, it must be ensured that the surface of the microsphere is completely covered by the colloid. The stripper prepared by the above coating method can reach a maximum flow rate of 8BV / h when resurrecting the sulfone amine solution.
[0063] In some embodiments of the present invention, preferably, the aging time is ≥ 7 days. If it is less than 7 days, the colloid adhesion and stability on the surface of the stripping agent are not sufficient, which is manifested by the colloid falling off or the stripping rate fluctuating.
[0064] Another aspect of the present invention provides a hydrophobic remover for a nonionic surfactant, which is obtained by any of the above preparation methods.
[0065] The hydrophobic remover comprises porous polymer microspheres and a sol coated on the surface of the porous polymer microspheres; the pores of the porous polymer microspheres are loaded with boric acid, the porous polymer microspheres are prepared by suspension copolymerization of acrylate monomers and aliphatic diene crosslinking agents, and the pores are formed by adding a porogen during the polymerization process.
[0066] In another aspect, the present invention provides use of one or more hydrophobic removers in removing nonionic surfactants from organic solutions.
[0067] In some embodiments of the present invention, preferably, the stripping agent is used in the removal of nonionic surfactants in sulfolane.
[0068] In some embodiments of the present invention, more preferably, the removing agent is used in the removal of nonionic surfactants in sulfoneamine solutions.
[0069] In some embodiments of the present invention, preferably, the removing agent is used in the removal of nonionic surfactants in sulfone amine solution to provide a method for removing nonionic surfactants in sulfone amine solution, the method comprising:
[0070] The sulfone amine solution is first separated by electrodialysis to remove part of the alcohol amine, and the remaining solution is separated by the hydrophobic remover to remove the nonionic surfactant;
[0071] The solution from which the nonionic surfactant is separated and removed is mixed with the alcoholamine separated by electrodialysis to obtain a sulfoneamine solution from which the nonionic surfactant is removed.
[0072] In some embodiments of the present invention, preferably, the percentage of alcoholamine separated by electrodialysis is ≥ 80%.
[0073] Alkylamine is weakly alkaline, and its ionization effect on boric acid (the active component of complex adsorption nonionic surfactant) in water increases with the increase of concentration, and vice versa. When the concentration of alcoholamine in the desulfurization solution is reduced to below 10%, its promoting effect on the ionization of boric acid is relatively small. To reduce the concentration of alcoholamine in the desulfurization solution to below 10%, 78% or more of alcoholamine needs to be separated.
[0074] In some embodiments of the present invention, preferably, when separating alcoholamines by electrodialysis, a sulfonic acid-based cation exchange membrane and a quaternary ammonium-based anion exchange membrane are used.
[0075] The electrodialysis method has a better separation effect on substances with stronger ionization ability. Alcoholamine is a weak electrolyte. The quaternary ammonium group of the quaternary amino anion exchange membrane has strong electron absorption, and the sulfonic acid group of the sulfonic acid cation exchange membrane has strong electron dissipation. They can respectively generate strong "attraction" for the anions and cations ionized by the alcoholamine, thereby promoting their ionization and achieving a removal rate of more than 85%.
[0076] In some embodiments of the present invention, the nonionic surfactant in the organic solution is preferably removed by soaking or rinsing.
[0077] In some embodiments of the present invention, it is more preferred to remove the nonionic surfactant in the organic solution by elution. Compared with the immersion method, the elution method can form a larger concentration difference, that is, the difference between the concentration of the nonionic surfactant in the solution and the concentration of the nonionic surfactant on the stripping agent, so the removal rate is higher.
[0078] In some embodiments of the present invention, preferably, the operating parameters for removing the nonionic surfactant from the sulfone amine solution by elution include: normal temperature and pressure, and the flow rate of the sulfone amine solution eluting the hydrophobic removal agent is less than 9 BV / h.
[0079] In some embodiments of the present invention, more preferably, the flow rate of the sulfoneamine solution for eluting the hydrophobic removing agent is 2 BV / h to 3 BV / h.
[0080] The volume of resin loaded in the resin column is called bed volume, abbreviated as BV. If the flow rate of the solution through the resin column is 2BV / h~4BV / h, the volume of the solution passing through per hour is 2~4 times the volume of the resin bed. It takes a certain amount of time for the non-ionic surfactant in the solution to be adsorbed onto the remover. When using an adsorbent that has not been sol-coated, the flow rate is too fast, that is, after reaching 20BV / h or above, the removal rate is <60%. After the surface of the non-ionic surfactant remover is covered with colloid, its speed of adsorbing the non-ionic surfactant in the desulfurization solution decreases, and the contact time between the solution and the remover must be increased. After the flow rate reaches 9BV / h or above, the removal rate is <60%, preferably 2BV / h~3BV / h.
[0081] In some embodiments of the present invention, preferably, after the hydrophobic stripping agent is saturated with the nonionic surfactant, it is regenerated with a weakly polar or medium-polar organic solvent.
[0082] The interaction force between the nonionic surfactant molecules and the weakly polar or medium-polar organic solvent molecules is stronger than the interaction force between the nonionic surfactant molecules and the boric acid. The nonionic surfactant molecules can be separated from the boric acid and desorbed to achieve the regeneration of the hydrophobic remover.
[0083] In some embodiments of the present invention, more preferably, the weakly polar or medium-polar organic solvent is dichloromethane and / or ethyl acetate.
[0084] The beneficial effects of the present invention include:
[0085] 1) The hydrophobic desorbent of the present invention has high selectivity for the adsorption of nonionic surfactants and sulfolane. The active component boric acid in the pores of the porous polymer microspheres can be complexed with the nonionic surfactant entering, but not with the sulfolane, thereby achieving selective adsorption of the two, achieving deep removal of the nonionic surfactant in the sulfolane, and low sulfolane loss rate; at the same time, it can be ensured that no new impurities are introduced after the nonionic surfactant in the sulfolane is removed.
[0086] 2) When the desorbent of the present invention is not sol-coated, the removal rate of the nonionic surfactant in cyclopentane sulfone is as high as 98% or more, and the stability is good. The adsorption capacity of the desorbent can be maintained at more than 98% of the initial capacity after more than 100 saturation regeneration cycles; but when used in sulfone amine solution, the adsorption capacity of the desorbent is reduced to less than 90% of the initial capacity after 39 saturation and regeneration cycles. The poor stability leads to poor economic efficiency. The hydrophobic desorbent obtained after sol-coating modification has excellent stability and removal rate when applied to sulfone amine solution. The removal rate of the nonionic surfactant in the sulfone amine solution is as high as ≥98%, and the removal rate of the hydrophobic desorbent can be maintained at more than 98% of the initial removal rate after more than 100 saturation regeneration cycles; it has excellent economic efficiency and high practical value. DETAILED DESCRIPTION
[0087] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0088] The key to the technical solution of the present invention is to design and prepare a hydrophobic remover of a nonionic surfactant, wherein the hydrophobic remover comprises porous polymer microspheres and a sol coated on the surface of the porous polymer microspheres; the pores of the porous polymer microspheres are loaded with boric acid; the porous polymer microspheres are prepared by suspension copolymerization of acrylate monomers and aliphatic diene crosslinking agents, and the pores are formed by adding a porogen during the polymerization process; the sol is prepared by a sol-gel method from silicate and alkoxy silicon, wherein the structural formula of the alkoxy silicon is Wherein, R1 is a C1-C10 alkyl group, preferably a C1-C5 alkyl group, more preferably a methyl, ethyl or propyl group; R2 is a C5-C20 fluoroalkyl group, preferably a C9-C17 fluoroalkyl group, more preferably a nonafluorohexyl group, a tridecafluorooctyl group or a heptadecafluorodecyl group, and most preferably a heptadecafluorodecyl group. The silicate is preferably ethyl orthosilicate.
[0089] The remover of the present invention has high selectivity for nonionic surfactants and sulfolane, and can achieve the removal of nonionic surfactants in a desulfurization solution containing sulfolane. Specifically, the active component boric acid in the pores of the porous polymer microspheres can be complexed with the nonionic surfactant entering, but not with sulfolane, thereby achieving selective adsorption of the two, achieving deep removal of the nonionic surfactant in sulfolane, and a low sulfolane loss rate; at the same time, it can be ensured that no new impurities are introduced after the nonionic surfactant in sulfolane is removed. Further, the sol is modified and coated to be hydrophobic, which has a repelling effect on water molecules. When it is applied to the removal of nonionic surfactants in sulfoneamine desulfurization solutions, the contact probability between boric acid in the remover and water molecules in the desulfurization solution is greatly reduced, and the high organic molecule permeability of the colloid can ensure that the nonionic surfactant molecules pass through the colloid and contact with boric acid to be removed.
[0090] The present invention also specifically uses the hydrophobic remover to develop a corresponding method for removing nonionic surfactants from sulfoneamine solution, and reduces the concentration of alcoholamines in the desulfurization solution by designing a process route: the sulfoneamine solution is firstly separated by electrodialysis to remove part of the alcoholamines, and the remaining solution is separated and removed of the nonionic surfactants by the above hydrophobic remover. The solution from which the nonionic surfactants are separated and removed is mixed with the alcoholamines separated by electrodialysis to obtain a sulfoneamine solution from which the nonionic surfactants are removed.
[0091] Conventional polymer adsorbents are polymers formed by using styrene as a monomer and divinylbenzene as a crosslinking agent. Since sulfolane has a strong affinity for phenyl, this type of adsorbent has a strong adsorption effect on sulfolane. The porous polymer microspheres in the remover of the present invention are polymers prepared by using acrylate as a monomer and aliphatic diene as a crosslinking agent, and neither the monomer nor the crosslinking agent contains phenyl.
[0092] Sulfolane has a weak affinity for chain alkane molecules and a strong affinity for aromatic molecules. Therefore, the present invention does not select commonly used styrene as a monomer, but uses acrylate as a monomer. At the same time, the ester group in acrylate has a certain adsorption effect on sulfolane, but the alkyl group has a shielding effect on the effect of the ester group adsorbing sulfolane. The more carbon atoms in the alkyl group, the greater the shielding effect. However, if the number of alkyl groups is too large, a longer polyacrylate segment and a linear acrylate homopolymer may be generated during the polymerization reaction, causing the prepared remover to agglomerate during use. Among them, the number of alkyl groups in the hexyl acrylate molecule can best take into account the solution of the above two problems, satisfying that the shielding effect is large enough to have a very weak adsorption effect on sulfolane, and the remover will not agglomerate during use. Therefore, the acrylate monomer of the present invention is most preferably hexyl acrylate.
[0093] The polymer stripping agent of the present invention selects aliphatic diene as a crosslinking agent, and does not select conventional phenyl-containing divinylbenzene as a crosslinking agent because phenyl can adsorb cyclopentane. The preferred ethylene glycol dimethacrylate can increase the swelling degree of the copolymer, and the interchain distance of the finally obtained polymer is conducive to the penetration of nonionic surfactants with larger molecular weight.
[0094] The micropores prepared by the porogens n-decane, decanol, and 2-ethyl-1-hexanoic acid preferably used in the present invention have a pore size that is suitable for the subsequent introduction of the active component boric acid, but the pore size is not too large to weaken the potential energy superposition effect of each plane. Other porogens either make the active component boric acid loading amount low, or lead to weak adsorption of non-ionic surfactants, resulting in the problem of a small amount of adsorbed non-ionic surfactant being resolved.
[0095] When preparing the porous polymer microspheres, the molar ratio of the acrylate monomer, the aliphatic diene crosslinker, and the porogen is preferably 1: (0.07-0.3): (0.1-0.8). When the amount of the crosslinker is higher than 0.3, the internal structure of the porous polymer microspheres obtained will be too tight, which will increase the resistance of the non-ionic surfactant molecules to shuttle inside the porous polymer microspheres, which is not conducive to adsorption or desorption during regeneration, and the removal rate is low. When the amount of the crosslinker is lower than 0.07, the porous polymer microspheres obtained will aggregate in the cyclopentane sulfone desulfurization solution. When the amount of the porogen is lower than 0.1, the pore capacity and specific surface area of the porous polymer microspheres obtained are too low, and the adsorption capacity <10 mg / g does not meet the use requirements. When the amount of the porogen is higher than 0.8, the porous polymer microspheres will have problems of poor strength and collapse of the internal pore structure. More preferably, the molar ratio of the acrylic acid ester monomer, the aliphatic diene crosslinking agent, and the porogen is preferably 1:(0.1-0.2):(0.5-0.6).
[0096] The particle size distribution of the porous polymer microspheres loaded with boric acid in the present invention is preferably 0.2 mm to 1.0 mm; the specific surface area is preferably 300 m 2 / g~400m 2 / g; the average pore diameter is preferably 50nm to 110nm; and the pore volume is preferably 1.5mL / g to 2.0mL / g.
[0097] The specific preparation method of the hydrophobic remover comprises the following steps:
[0098] Suspending and copolymerizing an acrylate monomer, an aliphatic diene crosslinking agent and a porogen in water to obtain porous polymer microspheres; soaking the porous polymer microspheres in a boric acid solution to load boric acid, and then filtering out the microspheres and drying them;
[0099] The surface of the porous polymer microspheres loaded with boric acid is coated with the sol, and then aged to obtain the hydrophobic removal agent.
[0100] In some specific embodiments, the sol is prepared by the following steps:
[0101] The silicate is mixed with ethanol, then added into acidic water and mixed, and then alkoxy silicon is added and mixed for 8 hours to 12 hours, and then allowed to stand for 20 hours to 40 hours to obtain the sol.
[0102] Silicate esters and alkoxy silicon are hydrolyzed in water and then polymerized to form sol. Ethanol is added to make silicate esters and alkoxy silicon miscible with water. Acid is added to adjust the water to be acidic in order to control the gelation rate and obtain a sol with uniform particle size distribution. The molecular structure and size of alkoxy silicon are the key to determining the pore size of the formed colloid. The pore size of the colloid made of the defined alkoxy silicon is suitable for non-ionic surfactant molecules.
[0103] In some specific embodiments, the molar ratio of silicate to ethanol is 1:(3-8). If the amount of ethanol is too large, not only the gelation speed is too slow, but also the particle size formed is too small. The hydrophobic remover prepared by using this sol has a low colloid permeability on the surface, which hinders the contact between non-ionic surfactant molecules and boric acid; if the amount of ethanol is too small, silicate, alkoxy silicon and water cannot be miscible. Therefore, the preferred molar ratio of silicate to ethanol in the present invention is 1:(3-8).
[0104] In some specific embodiments, the acidic water is adjusted to a pH of 1 to 6, preferably 2 to 3, by adding acid dropwise into the water.
[0105] If the hydrolysis is too fast under alkaline conditions, the sol will easily condense into blocks. If the acid is too strong and the gel formation is too slow, the size of the formed colloid particles will be uneven, and the required particle size of 2nm to 3nm particles only accounts for 48%. When the pH value is 2 to 3, a sol with uniform particle size can be formed, and the particle size of 2nm to 3nm particles accounts for more than 80%.
[0106] In some specific embodiments, the molar ratio of the silicate to water is 1:(0.5-1.1).
[0107] When the amount of water is too large (when the molar ratio of water to silicate is greater than 1.2), not only the gelation is slow, but also the viscosity of the formed sol is too low. The coating layer of the hydrophobic remover made by using this sol has the problem of falling off during use. When the amount of water is too low, the colloidal particles formed are uneven. Therefore, the preferred molar ratio of silicate to water in the present invention is 1: (0.5-1.1).
[0108] In some specific embodiments, the molar ratio of the silicate to the alkoxy silicon is 1:(0.6-1.5).
[0109] When the molar ratio of alkoxysilane to silicate is lower than 0.6, the hydrophobicity of the prepared colloid is insufficient; when it is higher than 1.5, the pores formed are too large and the hydrophobicity of the colloid does not meet the requirements.
[0110] In some specific embodiments, the boric acid solution is preferably a saturated boric acid solution at 80-90°C. High-concentration boric acid solution is conducive to the loading of boric acid, but the solubility of boric acid in cold water is very low. Increasing the temperature can increase its solubility; but when the temperature reaches above 90°C, the solution has a tendency to boil, which is not conducive to the deposition of boric acid on the microspheres. Therefore, the preferred boric acid solution of the present invention is a saturated boric acid solution at 80-90°C.
[0111] In some specific embodiments, the mass ratio of the boric acid to the porous polymer microspheres is greater than 0.1. Too little boric acid will result in the adsorption capacity of the obtained stripping agent for nonionic surfactants being less than 10 mg / g, which does not meet the use requirements. More preferably, the mass ratio of the boric acid to the porous polymer microspheres is 0.7.
[0112] In some specific embodiments, the soaking time is greater than 0.5 h. More preferably, the soaking time is 5 h to 6 h. When the soaking time is less than 0.5 h, the adsorption capacity of the obtained remover for nonionic surfactant is less than 10 mg / g, which does not meet the use requirements. After the soaking time exceeds 6 h, the adsorption capacity of the remover no longer increases.
[0113] In some specific embodiments, the immersion temperature is 50-90° C. At this temperature, the solubility of boric acid is high. When the temperature is higher than 90° C., the solution tends to boil, which is not conducive to the deposition of boric acid on the microspheres.
[0114] In some specific embodiments, the drying temperature is 100-165° C., more preferably 120-140° C. When the drying temperature is higher than 165° C., boric acid tends to decompose into metaboric acid. 120-140° C. can ensure drying without decomposing boric acid and shorten the drying time.
[0115] In some specific embodiments, the specific process of the sol coating includes:
[0116] The porous polymer microspheres are arranged in a single layer in a container containing sol. The height of the sol in the container is 1 / 4 to 1 / 3 of the height of the remover particles. The porous polymer microspheres are rolled in the sol until the entire surface is covered with the sol, and the porous polymer microspheres are taken out.
[0117] The amount of sol applied should not be too much, otherwise the colloid on the surface of the stripper will be thicker, which will seriously reduce the adsorption rate of the non-ionic surfactant, resulting in insufficient removal rate. The colloid covering the surface of the microsphere should be as thin as possible, which is conducive to improving the rate and removal rate of the stripper adsorbing the non-ionic surfactant. At the same time, it must be ensured that the surface of the microsphere is completely covered by the colloid. The stripper prepared by the above coating method can reach a maximum flow rate of 8BV / h when resurrecting the sulfone amine solution.
[0118] In some specific embodiments, the aging time is ≥ 7 days. If it is less than 7 days, the colloid adhesion and stability on the surface of the remover are not sufficient, which is manifested by the colloid falling off or the removal rate fluctuating.
[0119] The hydrophobic remover of the present invention can be used to remove nonionic surfactants in organic solutions, especially in sulfolane, and more specifically in sulfoneamine solutions.
[0120] In some specific embodiments, the removing agent is used in the removal of non-ionic surfactant in sulfone amine solution to provide a method for removing non-ionic surfactant in sulfone amine solution, the method comprising:
[0121] The sulfone amine solution is first separated by electrodialysis to remove part of the alcohol amine, and the remaining solution is separated by the hydrophobic remover to remove the nonionic surfactant;
[0122] The solution from which the nonionic surfactant is separated and removed is mixed with the alcoholamine separated by electrodialysis to obtain a sulfoneamine solution from which the nonionic surfactant is removed.
[0123] In some embodiments, the percentage of alcoholamine separated by electrodialysis is ≥ 80%.
[0124] Alkylamine is weakly alkaline, and its ionization effect on boric acid (the active component of complex adsorption nonionic surfactant) in water increases with the increase of concentration, and vice versa. When the concentration of alcoholamine in the desulfurization solution is reduced to below 10%, its promoting effect on the ionization of boric acid is relatively small. To reduce the concentration of alcoholamine in the desulfurization solution to below 10%, 78% or more of alcoholamine needs to be separated.
[0125] In some specific embodiments, when separating alcoholamines by electrodialysis, a sulfonic acid-based cation exchange membrane and a quaternary ammonium-based anion exchange membrane are used.
[0126] The electrodialysis method has a better separation effect on substances with stronger ionization ability. Alcoholamine is a weak electrolyte. The quaternary ammonium group of the quaternary amino anion exchange membrane has strong electron absorption, and the sulfonic acid group of the sulfonic acid cation exchange membrane has strong electron dissipation. They can respectively generate strong "attraction" for the anions and cations ionized by the alcoholamine, thereby promoting their ionization and achieving a removal rate of more than 85%.
[0127] In some specific embodiments, the nonionic surfactant in the organic solution is removed by soaking or rinsing. More preferably, the nonionic surfactant in the organic solution is removed by rinsing. Compared with the soaking method, the rinsing method can form a larger concentration difference, that is, the difference between the concentration of the nonionic surfactant in the solution and the concentration of the nonionic surfactant on the stripping agent, so the removal rate is higher.
[0128] In some specific embodiments, the operating parameters for removing nonionic surfactants from sulfone amine solution by elution include: normal temperature and pressure, the flow rate of sulfone amine solution eluting hydrophobic removal agent is less than 9BV / h, preferably 2BV / h to 3BV / h.
[0129] The volume of resin loaded in the resin column is called bed volume, abbreviated as BV. If the flow rate of the solution through the resin column is 2BV / h~4BV / h, the volume of the solution passing through per hour is 2~4 times the volume of the resin bed. It takes a certain amount of time for the non-ionic surfactant in the solution to be adsorbed onto the remover. When using an adsorbent that has not been sol-coated, the flow rate is too fast, that is, after reaching 20BV / h or above, the removal rate is <60%. After the surface of the non-ionic surfactant remover is covered with colloid, its speed of adsorbing the non-ionic surfactant in the desulfurization solution decreases, and the contact time between the solution and the remover must be increased. After the flow rate reaches 9BV / h or above, the removal rate is <60%, preferably 2BV / h~3BV / h.
[0130] In addition, after the hydrophobic remover is saturated with the non-ionic surfactant, it can also be regenerated with a non-polar or medium-polar organic solvent. The interaction force between the non-ionic surfactant molecules and the non-polar or medium-polar organic solvent molecules is stronger than the interaction force between the non-ionic surfactant molecules and the boric acid molecules, and the non-ionic surfactant molecules can be separated from the boric acid to desorb and regenerate the remover. Preferably, the non-polar or medium-polar organic solvent is selected from at least one of dichloromethane and ethyl acetate.
[0131] In a preferred embodiment of the present invention, the acrylate monomer is hexyl acrylate, the aliphatic diene crosslinker is ethylene glycol dimethacrylate, the porogen is decane, decanol or 2-ethyl-1-hexanoic acid; the silicate is ethyl orthosilicate, and the alkoxysilane is heptadecafluorodecyltrimethyl (or ethyl or propyl)oxysilane.
[0132] Conventional polymer adsorbents are polymers formed with styrene as a monomer and divinylbenzene as a crosslinking agent. Since sulfolane has a strong affinity for phenyl, this type of adsorbent has a strong adsorption effect on sulfolane. The stripping agent of the present invention is a polymer prepared with acrylate as a monomer and aliphatic diene as a crosslinking agent, and neither the monomer nor the crosslinking agent contains phenyl. The ester group in acrylate has a certain adsorption effect on sulfolane, but the alkyl group has a shielding effect on the adsorption of sulfolane by the ester group, and the more carbon atoms in the alkyl group, the greater the shielding effect; however, if the number of alkyl groups is too large, a longer polyacrylate chain segment and a linear acrylate homopolymer may be generated during the polymerization reaction, causing the prepared stripping agent to clump during use. The number of alkyl groups in the hexyl acrylate molecule can solve the above two problems at the same time, satisfying that the shielding effect is large enough to have a weak adsorption effect on sulfolane, and the stripping agent will not clump during use. The preferred ethylene glycol dimethacrylate of cross-linking agent can increase the swelling degree of copolymer, and the interchain distance of the polymer obtained at last is large, which is not only conducive to the infiltration of organic substances with larger molecular weight of surfactant, but also the long-chain hydrocarbon group can further weaken the affinity of polymer to sulfolane and strengthen the affinity of polymer to non-ionic surfactant.Porosity-forming agent is used to make polymer into porous structure, so that surfactant molecule is located in pore, each plane in the gap acts simultaneously, potential energy produces superposition, and can strengthen the force between surfactant and stripping agent.Porosity-forming agent selects decane, decanol, 2-ethyl-1-hexanoic acid, so that the pore size of prepared porous polymer is suitable for subsequent active component introduction into pore, and the potential energy superposition effect of each plane is not too large to weaken.Boric acid is introduced and loaded on the surface of the inner hole of prepared porous polymer, because boric acid is an electron-deficient compound, and the oxygen on the polyoxyethylene of non-ionic surfactant can provide electrons to be complexed with the boron atom on boric acid, and sulfolane cannot be complexed with it, so the selective adsorption of non-ionic surfactant in sulfolane is realized.
[0133] The present invention further uses sol to coat and modify the desorbent to be hydrophobic. In the preferred embodiment, ethyl orthosilicate and heptadecafluorodecyltrimethyl(ethyl / propyl)oxysilane are hydrolyzed and polymerized to form a colloid with high water-repellency and high organic molecule permeability to cover the surface of the desorbent, thereby obtaining a hydrophobic desorbent. The desorbent modified in this way has a repelling effect on water molecules. When the desorbent is used to remove non-ionic surfactants from sulfoneamine solution, the contact probability between boric acid in the desorbent and water molecules in the desulfurization solution is greatly reduced. In addition, the high organic molecule permeability of the colloid can ensure that the non-ionic surfactant molecules pass through the colloid and come into contact with the boric acid to be removed.
[0134] The present invention provides some specific examples below to illustrate the present invention in more detail, wherein all numerical values specified (such as temperature, time, concentration and weight, etc., including the range of each thereof) are usually appropriately changed by (+) or (-) approximate values in increments of 0.1 or 1.0. All numerical values specified can be understood as being preceded by the term "about".
[0135] Example 1
[0136] The removal agents 1 to 13 that were not modified by sol coating were prepared according to the following steps, and their performance was tested.
[0137] 1. Preparation of the remover
[0138] 1) mixing a monomer, a cross-linking agent and a porogen in a molar ratio of 1:0.1:0.5 to obtain a mixture 1;
[0139] 2) mixing mixture 1 with benzoyl peroxide in a mass ratio of 100:1 to obtain mixture 2;
[0140] 3) mixing hydroxyethyl cellulose, sodium chloride and water in a mass ratio of 0.6:10:100 to obtain a mixture 3;
[0141] 4) Mix mixture 2 and mixture 3 at a ratio of 1:3, start the stirrer, heat to 60-90°C for 12 hours, filter out the microspheres, wash with anhydrous ethanol and deionized water for 4 times, and finally dry under vacuum at 60°C for 18 hours;
[0142] 5) Transfer the microspheres to a saturated boric acid solution at 70°C (the mass ratio of the boric acid solution to the microspheres is 4.2:1, the boric acid concentration of the saturated boric acid solution at 70°C is 16.7%, and the mass ratio of boric acid to the microspheres is 0.7:1) and soak for 5 hours. Filter the microspheres and bake at 130°C for 5 hours to obtain a remover.
[0143] Follow the above steps to obtain:
[0144] Remover 1: The monomer, cross-linking agent and porogen used are hexyl acrylate, ethylene glycol dimethacrylate and 2-ethyl-1-hexanoic acid, respectively.
[0145] Remover 2: The monomer, cross-linking agent and porogen used are methyl acrylate, ethylene glycol dimethacrylate and 2-ethyl-1-hexanoic acid, respectively.
[0146] Remover 3: The monomer, cross-linking agent and porogen used are styrene, ethylene glycol dimethacrylate and 2-ethyl-1-hexanoic acid, respectively.
[0147] Remover 4: The monomer, cross-linking agent and porogen used are hexyl acrylate, divinylbenzene and 2-ethyl-1-hexanoic acid, respectively.
[0148] Stripper 5: The monomers, crosslinking agent and porogen used are the same as those of Stripper 1, namely hexyl acrylate, ethylene glycol dimethacrylate and 2-ethyl-1-hexanoic acid, but the molar ratio is changed to 1:0.35:0.5.
[0149] Remover 6: The monomer, cross-linking agent and porogen used are hexyl acrylate, ethylene glycol dimethacrylate and isooctyl alcohol, respectively.
[0150] Remover 7: The monomer, crosslinker and porogen used are the same as those of Remover 1, namely hexyl acrylate, ethylene glycol dimethacrylate and 2-ethyl-1-hexanoic acid, but the molar ratio is changed to 1:0.1:0.05.
[0151] Remover 8: Step 5) The mass ratio of boric acid to microspheres was changed to 0.05:1.
[0152] Remover 9: Step 5) The immersion time of the microspheres in the 70°C boric acid solution was changed to 0.4 hours.
[0153] Remover 10: Step 5) Change the drying temperature of the microspheres to 166°C.
[0154] Remover 11: The monomer, cross-linking agent and porogen used are hexyl acrylate, ethylene glycol dimethacrylate and n-decane, respectively.
[0155] Remover 12: The monomer, cross-linking agent and porogen used are hexyl acrylate, ethylene glycol dimethacrylate and decanol, respectively.
[0156] Remover 13: The monomer and cross-linking agent used are hexyl acrylate and ethylene glycol dimethacrylate, respectively, and there is no porogen.
[0157] 2. Preparation of Sulfolane Solution
[0158] The most common nonionic surfactant in the natural gas desulfurization solution is polyoxyethylene alkyl alcohol ether-20. Polyoxyethylene alkyl alcohol ether-20 is added to sulfolane to prepare a sulfolane solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20.
[0159] 3. Remover performance test
[0160] The removers 1 to 13 and activated carbon were loaded into 14 glass columns with an inner diameter of 25 mm, and the loading amount was 25 g. More than 500 g of the prepared sulfolane solution was injected into the top of each of the 14 glass columns, and the solution was allowed to flow through the activated carbon or each remover from top to bottom at a speed of 4 BV / h. Finally, nitrogen was used to blow the activated carbon and the remover from the upper end of the glass column, and the sulfolane solution flowing out of the lower end of each glass column was collected and weighed m, and the mass fraction w of polyoxyethylene alkyl alcohol ether-20 in the sulfolane solution was determined. The removal rate and selective absorption ratio of activated carbon and each remover to non-ionic surfactants were calculated as follows:
[0161] Removal rate of nonionic surfactant = (0.4% × 500 – w × m) ÷ (0.4% × 500)
[0162] Use 100 mL of ethyl acetate to elute the activated carbon and each removing agent from top to bottom, respectively elute the polyoxyethylene alkyl alcohol ether-20 and cyclopentane sulfone adsorbed on the activated carbon and each removing agent, and determine the respective masses of the two substances (the mass of the eluent multiplied by the respective contents of the two substances in the eluent).
[0163] Selective absorption ratio = the amount of polyoxyethylene alkyl alcohol ether-20 eluted / the amount of sulfolane eluted
[0164] The removal rates and selective adsorption ratios of activated carbon and various removal agents for nonionic surfactants are shown in Table 1.
[0165] Table 1 Removal rate and selective absorption ratio of each remover for nonionic surfactant
[0166] Removal rate Selective absorption ratio Activated carbon 6.6% 0.1 Remover 1 98.3% 56.1 Remover 2 92% 18.5 Remover 3 51% 1.1 Remover 4 53% 1.2 Remover 5 57% 33.5 Remover 6 81% 47.6 Remover 7 6.3% 4.2 Remover 8 7.5% 5 Remover 9 10% 6.1 Remover 10 38% 22.4 Remover 11 96.5% 55.4 Remover 12 95.1% 55.9 Remover 13 6.1% 4.3
[0167] The experimental results shown in Table 1 show that the removers 3 and 4 made of phenyl-containing monomers or cross-linking agents not only have a selective adsorption ratio lower than 2, but also have a non-ionic surfactant removal rate of <60%; the remover 5 made with a molar ratio of cross-linking agent to monomer greater than 0.3 has selective adsorption for non-ionic surfactants in sulfolane, with a selective adsorption ratio of 33.5, much greater than 2, but a removal rate of <60%; the removers 7, 8, and 9 made with a mass ratio of porogen to monomer lower than 0.1, a mass ratio of boric acid to microspheres lower than 0.1, and a boric acid soaking time of less than 0.5 hours have very low removal rates of <20% because of their adsorption capacity <10 mg / g; the remover 10 made with the microsphere drying temperature changed to 166°C has a low removal rate of <40% because boric acid decomposes into metaboric acid.
[0168] The removal rate of the stripper 2 prepared by using methyl acrylate as the monomer can reach more than 90%, and the selective absorption ratio is greater than 10 (the loss rate of cyclopentane is less than 1%), which meets the requirements of actual production and use, but the selective absorption ratio of the stripper prepared by the most preferred monomer hexyl acrylate is higher than 50. The stripper 6 prepared by using isooctyl alcohol as the porogen has a selective absorption ratio of 47.5 and a relatively high removal rate of more than 80%, which meets the requirements of actual production and use, but the removal rate of the stripper prepared by the preferred porogens n-decane, decanol, and 2-ethyl-1-hexanoic acid is higher than 95%. The stripper 1 prepared by the most preferred conditions has very outstanding performance, with a removal rate higher than 98% and a selective absorption ratio of more than 56.
[0169] The particle size, specific surface area, average pore size and pore volume of the removers 1, 2, 6, 11 and 12 that meet the actual production requirements were measured by sieving method, respectively. The measurement results are shown in Table 2.
[0170] Table 2
[0171]
[0172] The test results shown in Table 2 show that the particle size distribution of the remover prepared under the optimal conditions is (0.2-1.0) mm; the specific surface area is (300-400) m 2 / g; the average pore diameter is (15~27)nm, and the pore volume is in the range of (1.5~2.0)mL / g.
[0173] Example 2
[0174] This example explores the removal effect of the remover 1 on the non-ionic surfactant at different flow rates.
[0175] The remover 1 was loaded into 6 glass columns with an inner diameter of 25 mm, and the loading amount was 25 g. The 6 glass columns were numbered 1 # ~6 # 500 g of sulfolane solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was injected into the top of each of the six glass columns, and the solution was allowed to flow through each glass column from top to bottom at a certain flow rate. # ~6 # The flow rates are 0.1BV / h, 2BV / h, 4BV / h, 6BV / h, 7BV / h, and 20BV / h, and finally, nitrogen is used to blow activated carbon and the remover from the upper end of the glass column. The sulfolane solution flowing out of the lower end of each glass column is collected and weighed m, and the mass fraction w of polyoxyethylene alkyl alcohol ether-20 in the sulfolane solution is determined. The removal rate and selective absorption ratio of the remover to the non-ionic surfactant are calculated as follows:
[0176] Removal rate of nonionic surfactant = (0.4% × 500 – w × m) ÷ (0.4% × 500)
[0177] The removal rate of nonionic surfactant by remover 1 at different flow rates is shown in Table 3.
[0178] Table 3 Removal rate of nonionic surfactant by remover 1 at different flow rates
[0179] <![CDATA[1 # Pillar]]> <![CDATA[2 # Pillar]]> <![CDATA[3 # Pillar]]> <![CDATA[4 # Pillar]]> <![CDATA[5 # Pillar]]> <![CDATA[6 # Pillar]]> Solution flow rate 0.1BV / h 2BV / h 4BV / h 6BV / h 7BV / h 20BV / h Removal rate 83.7% 98.5% 98.5% 98.3% 93.2% 59.4%
[0180] The experimental results shown in Table 3 show that the removal rate when the solution flow rate is 4BV / h to 6BV / h is basically the same as that when the flow rate is 2BV / h, both of which can reach more than 98%. A faster flow rate is beneficial to saving solution treatment time, so it is better; but when the flow rate is too fast, the removal rate will be reduced due to insufficient contact time. When the solution increases to 7BV / h, the removal rate decreases to 93.2%. When it increases to 20BV / h, the removal rate is less than 60%. When the flow rate is too low at 0.1BV / h, which is close to the immersion method, the removal rate is not high enough, less than 85%, so it is preferred to treat the solution by 4BV / h to 6BV / h elution removal agent.
[0181] Example 3
[0182] This example uses different regeneration liquids to regenerate the stripping agent, and verifies the removal effect of the stripping agent on the non-ionic surfactant after regeneration.
[0183] 1) 2 in Example 2 # Column, 3 # Column, 4 # After the columns were regenerated by eluting with 100 ml of ethanol, dichloromethane and ethyl acetate respectively, 500 g of sulfolane solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was injected into the top of the two glass columns respectively. The solution flow rate was 4 BV / h. The removal rate of the non-ionic surfactant by the remover 1 after regeneration with ethanol, dichloromethane and ethyl acetate was tested. The test results are shown in Table 4.
[0184] Table 4 Removal rate of nonionic surfactant by remover 1 after regeneration with different regeneration solutions
[0185] <![CDATA[2 # Pillar]]> <![CDATA[3 # Pillar]]> <![CDATA[4 # Pillar]]> Regeneration fluid Ethanol Dichloromethane Ethyl acetate Removal rate 56.8% 98.3% 98.2%
[0186] The experimental results shown in Table 4 show that after using ethanol to regenerate the removal agent 1, its removal rate dropped significantly to below 60%; using dichloromethane and ethyl acetate to regenerate the removal agent 1, its removal rate can be maintained above 98%.
[0187] 2) Continue to elute and regenerate column 3# and column 4# with 100 ml of dichloromethane and ethyl acetate respectively, then inject 500 g of sulfolane solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 at the top of the two glass columns respectively, and the solution flow rate is 4 BV / h. Repeat the above operation to test the removal rate of the remover 1 after multiple regenerations, and the measurement results are shown in Table 5.
[0188] Table 5 Removal rate of nonionic surfactant after multiple regeneration of remover 1
[0189]
[0190] The experimental results shown in Table 5 show that when the remover 1 is used to remove nonionic surfactants in sulfolane solution, the removal rate can be maintained at more than 98% of the initial removal rate after more than 100 saturation and regeneration cycles, and the stability is good.
[0191] Example 4
[0192] The hydrophobic removers 1 to 7 were prepared according to the following steps and their performance was tested.
[0193] 1. Preparation of hydrophobic removers 1 to 7
[0194] 1) TEOS is mixed with ethanol, then added into water adjusted to pH 3 (pH of water is adjusted with hydrochloric acid), stirred and mixed, then fluorosilane is added, stirred for 8 hours, and allowed to stand for 20 hours to obtain a sol. The molar ratio of TEOS: ethanol: water: fluorosilane is 1:3:0.5:0.6.
[0195] 2) Arrange the nonionic surfactant remover particles (remover 1) in a single layer in a container containing the sol prepared in step 1), wherein the height of the sol in the container is 1 / 4 of the height of the remover particles. Roll the remover in the sol until the entire surface of the remover is covered with the sol, and then take out the remover.
[0196] 3) The stripping agent after the second step of sol coating is aged for 7 days.
[0197] Follow the above steps to obtain:
[0198] Hydrophobic remover 1: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane;
[0199] Hydrophobic remover 2: The fluorosilane used in step 1) is tridecafluorooctyltrimethoxysilane;
[0200] Hydrophobic remover 3: The fluorosilane used in step 1) is nonafluorohexyltriethoxysilane;
[0201] Hydrophobic remover 4: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the molar ratio of tetraethyl orthosilicate and ethanol is changed to 1:9, that is, the molar ratio of tetraethyl orthosilicate:ethanol:water:fluorosilane is 1:9:0.5:0.6.
[0202] Hydrophobic remover 5: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the pH value of the water is adjusted to a hydrochloric acid concentration of 0.2 mol / L, at which time the pH is less than 1, about 0.7.
[0203] Hydrophobic remover 6: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the pH value of the water is adjusted to 1 instead.
[0204] Hydrophobic remover 7: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the molar ratio of ethyl silicate and water is changed to 1:0.4, that is, the molar ratio of ethyl orthosilicate: ethanol: water: fluorosilane is 1:3:0.4:0.6.
[0205] 2. Preparation of sulfoneamine solution
[0206] Polyoxyethylene alkyl alcohol ether-20 was added into a sulfone amine solution (sulfolane: N-methyldiethanolamine: water mass ratio = 25:45:30) to prepare a sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20.
[0207] 3. Hydrophobic remover performance test
[0208] 1) Hydrophobic removing agents 1-7 were respectively loaded into 7 glass columns with an inner diameter of 25 mm, with a loading amount of 25 g each.
[0209] 2) 3500g of the above-mentioned sulfoneamine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 is evenly divided into 7 parts, and 80% N-methyldiethanolamine is first separated by electrodialysis in each solution, and then injected into the above-mentioned 7 glass columns (injected from the top of the glass column), allowing the solution to flow through each stripping agent from top to bottom at a speed of 4BV / h, blowing nitrogen from the top of the glass column to remove the stripping agent, and collecting the solution flowing out of the bottom of each glass column in seven beakers, respectively, adding the N-methyldiethanolamine separated and removed by the electrodialysis instrument to the solution in each beaker, and weighing m, and measuring the mass fraction w of polyoxyethylene alkyl alcohol ether-20 in the solution.
[0210] The electrodialysis method specifically includes the following steps: the anion and cation membranes are selected as quaternary ammonium anion exchange membrane and sulfonic acid cation exchange membrane respectively. The solution is added to the electrodialyser, the power is turned on, the voltage value is adjusted to 220V, and after running for 5 minutes, the solution in the concentration chamber is taken out, which is the separated alcoholamine, and the solution in the desalination chamber is injected into the glass column to continue the non-ionic surfactant removal treatment.
[0211] 3) Calculate the removal rate of each hydrophobic remover on the nonionic surfactant, the calculation method is as follows:
[0212] Removal rate of nonionic surfactant = (0.4% × 400-w × m) ÷ (0.4% × 400)
[0213] The removal rate of each hydrophobic remover for non-ionic surfactant is shown in Table 6.
[0214] Table 6 Removal rate of nonionic surfactants by various hydrophobic removers
[0215]
[0216] The experimental results shown in Table 6 show that the hydrophobic remover 2 and the hydrophobic remover 3 are coated with sols made of tridecafluorooctyl trimethoxysilane and nonafluorohexyl triethoxysilane, respectively, and the nonionic surfactant removal rate is low <60%; the hydrophobic remover 4 is coated with a sol with too much ethanol, and the acidity of the sol preparation of the hydrophobic remover 5 is too strong. These factors all lead to a low nonionic surfactant removal rate of <60%; the acidity of the sol preparation of the hydrophobic remover 6 is pH = 1, although the removal rate reaches more than 60%, it is not optimal. The hydrophobic remover 1 prepared under the preferred conditions has a very high nonionic surfactant removal rate of >98%.
[0217] Example 5
[0218] 1. Preparation of hydrophobic removers 8 to 10
[0219] The preparation of the hydrophobic stripping agent is the same as in Example 4.
[0220] Removal agent 8: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the molar ratio of ethyl orthosilicate and heptadecafluorodecyltrimethoxysilane is changed to 1:0.5, that is, the molar ratio of ethyl orthosilicate: ethanol: water: fluorosilane is 1:3:0.4:0.5.
[0221] Removal agent 9: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the molar ratio of ethyl orthosilicate and heptadecafluorodecyltrimethoxysilane is changed to 1:1.6, that is, the molar ratio of ethyl orthosilicate: ethanol: water: fluorosilane is 1:3:0.4:1.6.
[0222] Removal agent 10: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the molar ratio of ethyl silicate to heptadecafluorodecyltrimethoxysilane is changed to 1:1.5, that is, the molar ratio of ethyl orthosilicate: ethanol: water: fluorosilane is 1:3:0.4:0.5.
[0223] 2. Preparation of sulfoneamine solution
[0224] Sulfolane: N-methyldiethanolamine: water is prepared in a mass ratio of 25:45:30 to prepare a sulfoneamine solution without a nonionic surfactant.
[0225] 3. Hydrophobic remover performance test
[0226] 25 g of each of hydrophobic remover 1 and hydrophobic remover 8-10 were placed in 200 g of sulfone amine solution without non-ionic surfactant, and shaken at 150 rpm for 40 days. The removers were separated and the performance of the removers was tested according to the method described in the third item of Example 1. The test results are shown in Table 7.
[0227] Table 7 Removal rate of each remover for nonionic surfactant
[0228] Hydrophobic remover 1 Hydrophobic remover 8 Hydrophobic remover 9 Hydrophobic remover 10 Removal rate 98.0% 92.0% 92.9% 98.1%
[0229] The experimental results shown in Table 7 show that the hydrophobic removal agent prepared by the molar ratio of heptadecafluorodecyltrimethoxysilane to tetraethyl orthosilicate of 0.6 and 1.5 has good stability. After soaking in sulfoneamine solution for 40 days, its removal rate can still be maintained at about 98%; however, the stability of the hydrophobic removal agent prepared by the molar ratio of heptadecafluorodecyltrimethoxysilane to tetraethyl orthosilicate of 0.5 and 1.6 is poor. After soaking in sulfoneamine solution for 40 days, its removal rate has not reached 95% of the initial removal rate.
[0230] Example 6
[0231] 1. Preparation of hydrophobic remover 11
[0232] The preparation of the hydrophobic stripping agent is the same as in Example 4.
[0233] Remover 11: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but step 2) is changed to an immersion method for applying the remover.
[0234] 2. Hydrophobic remover performance test
[0235] The hydrophobic remover 1 was loaded into 9 glass columns with an inner diameter of 25 mm, and the loading amount was 25 g. The 9 glass columns were numbered 1 # -9 # The performance of the removers was tested according to the method described in the third item of Example 4, except that the speed at which the sulfone amine solution containing a nonionic surfactant flows through each remover from top to bottom is 0.1, 1, 2, 3, 4, 6, 7, 8, and 9 BV / h, respectively. The test results are shown in Table 8.
[0236] Table 8 Removal rate of nonionic surfactant by hydrophobic remover 1 at different flow rates
[0237]
[0238] The hydrophobic remover 11 was loaded into 9 glass columns with an inner diameter of 25 mm, and the loading amount was 25 g. The 9 glass columns were numbered 10 and 11. # -17 # The performance of the removers was tested according to the method described in the third item of Example 4, except that the speed at which the sulfone amine solution containing a nonionic surfactant flows through each remover from top to bottom is 0.1, 1, 2, 3, 4, 6, 7, and 8 BV / h, respectively. The test results are shown in Table 9.
[0239] Table 9 Removal rate of nonionic surfactant by hydrophobic remover 11 at different flow rates
[0240]
[0241]
[0242] The experimental results shown in Table 8 show that the optimal flow rate for eluting the hydrophobic remover with sulfoneamine solution is 2BV / h to 3BV / h. Compared with the results in Table 2, after the surface of the nonionic surfactant remover is covered with colloid, the speed of its adsorption of the nonionic surfactant in the desulfurization solution decreases, and the contact time between the solution and the remover must be increased. When the flow rate reaches 9BV / h or above, the removal rate is less than 60%, preferably 2BV / h to 3BV / h.
[0243] By comparing the experimental results shown in Table 8 and Table 9, it can be seen that the hydrophobic remover prepared by coating the remover by immersion has a lower removal rate than the hydrophobic remover prepared by the preferred coating method at the same flow rate.
[0244] Example 7
[0245] 1. Preparation of hydrophobic remover 12
[0246] The preparation of the hydrophobic stripping agent is the same as in Example 4.
[0247] Removal agent 12: The fluorosilane used in step 1) is heptadecafluorodecyltrimethoxysilane, but the aging time after the removal agent is applied to the sol in step 3) is changed to 6 days.
[0248] 2. Hydrophobic remover performance test
[0249] The performance of hydrophobic remover 1 and hydrophobic remover 12 were tested according to the method described in the third item of Example 4, except that after treating 500 g of sulfoneamine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20, the hydrophobic remover was regenerated with ethyl acetate, and then the performance of the regenerated hydrophobic remover was tested. The test results are shown in Table 10.
[0250] Table 10 Removal rate of hydrophobic remover 1 and hydrophobic remover 12 after regeneration
[0251]
[0252] The experimental results shown in Table 10 show that the stability of the hydrophobic removal agent 1 prepared with a sol formation time of 7 days after regeneration is very good, but when the sol formation time is less than 6 days, the stability of the hydrophobic removal agent 12 prepared after regeneration is not good.
[0253] Example 8
[0254] 1) Fill 25g of activated carbon into a glass column No. 18 with an inner diameter of 25mm; # and 22 # 25 g of the uncoated sol remover 1 was filled into a glass column with an inner diameter of 25 mm; the hydrophobic remover 1 was filled into two glass columns with an inner diameter of 25 mm (numbered 20 # ,twenty one # ), the filling amount is 25g.
[0255] 2) Inject 500 g of sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 into the above 18 # The solution was allowed to flow through the activated carbon from top to bottom at a speed of 4 BV / h in a glass column (injected from the top of the glass column) to test the removal rate of polyoxyethylene alkyl alcohol ether-20 by the active agent.
[0256] 3) 500 g of sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was injected into the above 19 # The solution was allowed to flow from top to bottom through the unhydrophobically modified remover 1 at a rate of 4 BV / h in a glass column (injected from the top of the glass column), and then the remover was regenerated with ethyl acetate. After regeneration, the above operation was repeated to test the removal rate of the regenerated remover 1.
[0257] 4) 500 g of sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was first separated by electrodialysis to obtain 75% N-methyldiethanolamine, and then injected into the above 20 # The solution was allowed to flow through the hydrophobic remover 1 from top to bottom at a speed of 4 BV / h in a glass column (injected from the top of the glass column), and then the hydrophobic remover 1 was regenerated with ethyl acetate. After regeneration, the above operation was repeated to test the removal rate of the hydrophobic remover 1 after regeneration.
[0258] 5) 500 g of sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was first separated by electrodialysis to obtain 80% of N-methyldiethanolamine, and then injected into the above 21 #The solution was allowed to flow through the hydrophobic remover 1 from top to bottom at a speed of 4 BV / h in a glass column (injected from the top of the glass column), and then the hydrophobic remover 1 was regenerated with ethyl acetate. After regeneration, the above operation was repeated to test the removal rate of the hydrophobic remover 1 after regeneration.
[0259] 6) 500 g of sulfone amine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20 was first separated by electrodialysis to obtain 80% of N-methyldiethanolamine, and then injected into the above 22 # The solution was allowed to flow from top to bottom through the unhydrophobically modified remover 1 at a rate of 4 BV / h in a glass column (injected from the top of the glass column), and then the remover 1 was regenerated with ethyl acetate. After regeneration, the above operation was repeated to test the removal rate of the regenerated remover 1.
[0260] The test results are shown in Table 11.
[0261] Table 11
[0262]
[0263]
[0264] The experimental results shown in Table 11 are as follows:
[0265] ① The separation effect of using the existing activated carbon to separate polyoxyethylene alkyl alcohol ether-20 from the sulfoneamine solution is very poor, with a removal rate of only 6.5%;
[0266] ② When a nonionic surfactant remover without hydrophobic modification is used to directly treat a sulfoneamine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20, after the remover is regenerated 40 times, its removal rate is reduced to 86.3% (<90%) of the initial removal rate, and the stability is poor; even if 80% of the alcoholamine is separated by electrodialysis before treatment, after the remover is regenerated 80 times, its removal rate is reduced to 83.5% (<85%) of the initial removal rate, and the stability is poor;
[0267] ③ A hydrophobic remover was used to treat a sulfoneamine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20. Before the treatment, 75% of the alcoholamine was separated by electrodialysis. After the remover was regenerated 40 times, its removal rate was close to the initial removal rate. After regeneration 101 times, the removal rate was 96.0% (>95%) of the initial removal rate, and the stability was good.
[0268] ④ A hydrophobic remover was used to treat a sulfoneamine solution containing 0.4% (mass fraction) of polyoxyethylene alkyl alcohol ether-20. Before the treatment, 80% of the alcoholamine was separated by electrodialysis. After the remover was regenerated 101 times, the removal rate could still reach 98.9% (>98%) of the initial removal rate, and the stability was very good.
[0269] Combined with the data in point ②, point ③ and Table 5, the nonionic surfactant removal agent without hydrophobic modification in the present invention has a removal rate of more than 98% for nonionic surfactant in sulfolane, and its removal rate can be maintained at more than 98% of the initial removal rate after saturation and regeneration cycles for more than 100 times; however, when used for the sulfoneamine desulfurization solution of sulfolane and alcoholamine, there is a problem that the active component boric acid of the removal agent is slowly lost, resulting in a gradual decrease in the removal rate of the removal agent. After saturation and regeneration cycles of 80 times, the removal rate of the removal agent is reduced to less than 84% of the initial removal rate, and the poor stability leads to poor economy. The present invention has been found through research that the reason for the slow loss of active component boric acid is that alcoholamine promotes the dissolution of boric acid. Originally, boric acid is not easy to dissolve in cold water. Alcoholamine is weakly alkaline, and its ionized hydroxide in water promotes partial ionization of boric acid in water, increasing its solubility in the desulfurization solution. The higher the concentration of alcoholamine, the greater its promotion effect. The sulfone amine solution was treated with a hydrophobic remover, and 80% of the alcohol amine was separated by electrodialysis before the treatment. After the remover was regenerated 101 times, the removal rate could still reach 98.9% of the initial removal rate, and the stability was very good.
[0270] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a hydrophobic remover of a nonionic surfactant, wherein: The preparation method comprises the following steps: Suspending and copolymerizing an acrylate monomer, an aliphatic diene crosslinking agent and a porogen in water to obtain porous polymer microspheres; soaking the porous polymer microspheres in a boric acid solution to load boric acid, and then filtering out the microspheres and drying them; The surface of the porous polymer microspheres loaded with boric acid is coated with sol, and then aged to obtain the hydrophobic removal agent; The sol is prepared from silicate and alkoxy silicon by a sol-gel method, wherein the structural formula of the alkoxy silicon is Wherein, R1 is a C1-C10 alkyl group, and R2 is a C5-C20 fluoroalkyl group.
2. The preparation method according to claim 1, wherein The silicate is ethyl orthosilicate.
3. The preparation method according to claim 1, wherein In the alkoxy silicon, R1 is a C1-C5 alkyl group, and R2 is a nonafluorohexyl group, a tridecafluorooctyl group or a heptadecafluorodecyl group.
4. The preparation method according to claim 1, wherein The structural formula of the acrylate monomer is: Wherein R is a C1-C5 alkyl group.
5. The preparation method according to claim 1, wherein The aliphatic diene crosslinking agent is ethylene glycol dimethacrylate.
6. The preparation method according to claim 1, wherein The porogen is selected from at least one of isooctyl alcohol, n-decane, decanol, and 2-ethyl-1-hexanoic acid.
7. The preparation method according to claim 1, wherein The molar ratio of the acrylic acid ester monomer, the aliphatic diene crosslinking agent and the porogen is 1:(0.07-0.3):(0.1-0.8).
8. The preparation method according to claim 1, wherein The particle size distribution of the porous polymer microspheres is 0.2 mm to 1.0 mm; The specific surface area of the porous polymer microspheres loaded with boric acid is 300 m 2 / g~400m 2 / g, the average pore diameter is 50nm~110nm, and the pore volume is 1.5mL / g~2.0mL / g.
9. The preparation method according to claim 1, wherein The sol is prepared by the following steps: The silicate is mixed with ethanol, then added into acidic water and mixed, and then alkoxysilicon is added and mixed for 8h to 12h, and then allowed to stand for 20h to 40h to obtain the sol; the molar ratio of the silicate to ethanol is 1:(3-8); the molar ratio of the silicate to alkoxysilicon is 1:(0.6-1.5).
10. The preparation method according to claim 9, wherein: The acidic water is adjusted to a pH of 2 to 3 by adding acid dropwise into the water.
11. The preparation method according to claim 9, wherein: The molar ratio of the silicate to water is 1:(0.5-1.1).
12. The preparation method according to claim 1, wherein: The boric acid solution is a saturated boric acid solution at 80-90°C.
13. The preparation method according to claim 1, wherein: The mass ratio of the boric acid to the porous polymer microspheres is greater than 0.
1.
14. The preparation method according to claim 1, wherein: The soaking time is greater than 0.5 h, and the soaking temperature is 50-90° C.
15. The preparation method according to claim 1, wherein: The drying temperature is 100-165°C.
16. A hydrophobic remover of a nonionic surfactant, obtained by the preparation method according to any one of claims 1 to 15.
17. Use of the removing agent according to claim 16 in removing nonionic surfactants from organic solutions.
18. A method for removing nonionic surfactant from a sulfone amine solution, wherein: The method comprises: The sulfone amine solution is first separated by electrodialysis to remove part of the alcohol amine, and the remaining solution is separated and the non-ionic surfactant is removed by the hydrophobic removal agent according to claim 16; The solution from which the nonionic surfactant is separated and removed is mixed with the alcoholamine separated by electrodialysis to obtain a sulfoneamine solution from which the nonionic surfactant is removed.
19. The method according to claim 18, wherein: The percentage of alcohol amine separated by electrodialysis is ≥80%; When separating alcohol amines by electrodialysis, sulfonic acid-based cation exchange membranes and quaternary ammonium-based anion exchange membranes are used.
20. The use according to claim 17 or the method according to claim 18, wherein: Removing nonionic surfactants from organic solutions or sulfone amine solutions by soaking or eluting; The operating parameters for removing the nonionic surfactant from the sulfone amine solution by elution include: normal temperature and pressure, and the flow rate of the sulfone amine solution eluting the hydrophobic removal agent is less than 9BV / h.
21. The method according to claim 20, wherein: The flow rate of the sulfoneamine solution for eluting the hydrophobic removing agent is 2 BV / h to 3 BV / h.
22. The use or method of claim 20, wherein: After the stripping agent is saturated with the nonionic surfactant, it is regenerated with a weak polar or medium polar organic solvent.
23. The use or method according to claim 22, wherein: The weakly polar or medium polar organic solvent is selected from dichloromethane and / or ethyl acetate.
Citation Information
Patent Citations
Novel strongly and weakly alkaline anion exchange resin and preparation method thereof
CN102189008A
Pretreatment method of nonionic surfactant wastewater
CN104310665A
Regenerating method for inferior sulfolane solvent
CN106957297A
Regeneration process for inferior sulfolane
CN1076726C
Treatment method for surfactant-containing wastewater
CN107935236A
